SNX3 recruits to phagosomes and negatively regulates phagocytosis in dendritic cells. Issue 1 (8th April 2013) - Chua, Rong Yuan Ray; Wong, Siew Heng
Summary Phagocytes such as dendritic cells (DC) and macrophages employ phagocytosis to take up pathogenic bacteria into phagosomes, digest the bacteria and present the bacteria‐derived peptide antigens to the adaptive immunity. Hence, efficient antigen presentation depends greatly on a well‐regulated phagocytosis process. Lipids, particularly phosphoinositides, are critical components of the phagosomes. Phosphatidylinositol‐3, 4, 5‐triphosphate [PI(3, 4, 5)P3] is formed at the phagocytic cup, and as the phagosome seals off from the plasma membrane, rapid disappearance of PI(3, 4, 5)P3 is accompanied by high levels of phosphatidylinositol‐3‐phosphate (PI3P) formation. The sorting nexin (SNX) family consists of a diverse group of Phox‐homology (PX) domain‐containing cytoplasmic and membrane‐associated proteins that are potential effectors of phosphoinositides. We hypothesized that SNX3, a small sorting nexin that contains a single PI3P lipid‐binding PX domain as its only protein domain, localizes to phagosomes and regulates phagocytosis in DC. Our results show that SNX3 recruits to nascent phagosomes and silencing of SNX3 enhances phagocytic uptake of bacteria by DC. Furthermore, SNX3 competes with PI3P lipid‐binding protein, early endosome antigen‐1 (EEA1) recruiting to membranes. Our results indicate that SNX3 negatively regulates phagocytosis in DC possibly by modulating recruitment of essential PI3P lipid‐binding proteins of the phagocytic pathways, such as EEA1, to phagosomal membranes.